EXPERIENCE IN THE APPLICATION OF NEURO-LINGUISTIC TECHNOLOGIES FOR THE TRAINING OF FUTURE SPECIALISTS IN THE EDUCATIONAL AND INFORMATION ENVIRONMENT OF THE TECHNICAL UNIVERSITY - Rakhmanov, Vitalii (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article presents the experience of using neuro-linguistic technologies in the educational process of a technical university, which has a significant impact on the quality of education and the effectiveness of future specialists. The purpose of the article is to implement the experience of using neuro-linguistic technologies to solve educational tasks in future activities. This helps create personalized learning approaches and resources that take into account each student's needs and learning style. The use of automated systems for monitoring and measuring the effectiveness of knowledge contributes to the objective assessment of the competences of future specialists. The task of the research is to reveal the experience of using neuro-linguistic technologies, which will help to create more accessible and integrated educational materials, including virtual laboratories, interactive textbooks and other resources. Research methods consist in the study and generalization of domestic and foreign experience for the formation of conceptual provisions for the training of future specialists in the conditions of an educational and informational environment, scientific analysis, as well as observation of the educational process. The results. The proposed technologies can provide individual training of future specialists with different directions and level of preparation, as well as improve the educational process. Large volumes of data collected thanks to neuro-linguistic technologies can be used to analyze and improve the educational process. The use of neuro-linguistic technologies can make education accessible to students from different countries and language groups. Interactive classes built on the basis of neuro-linguistic technologies increase the motivation of future specialists to study. Conclusion. The successful implementation of neuro-linguistic technologies in the educational process helps to plan, organize, provide and monitor the training of future specialists